Fragmentation of CD+ induced by intense ultrashort laser pulses - Graham, L.; Zohrabi Alaei, Mohammad; Gaire, B.; Ablikim, U.; Jochim, B.; Berry, B.; Severt, T.; Betsch, K. J.; Summers, A. M.; Lev, U.; Heber, O.; Zajfman, D.; et al. (My University, 2015)
The fragmentation of CD[superscript +] in intense ultrashort laser pulses was investigated using a coincidence three-dimensional momentum imaging technique improved by employing both transverse and longitudinal electric fields. This allowed clear separation of all fragmentation channels and the determination of the kinetic energy release down to nearly zero, for a molecule with significant mass asymmetry. The most probable dissociation pathways for the two lowest dissociation limits, C[superscript +]+D and C+D[superscript +], were identified for both 22-fs, 798-nm and 50-fs, 392-nm pulses. Curiously, the charge asymmetric dissociation of CD[superscript 2+] was not observed for 392-nm photons, even though it was clearly visible for the fundamental 798 nm at the same peak intensity.
Citation: Graham, L., Zohrabi, M., Gaire, B., Ablikim, U., Jochim, B., Berry, B., . . . Ben-Itzhak, I. (2015). Fragmentation of CD+ induced by intense ultrashort laser pulses. Physical Review A, 91(2), 11. doi:10.1103/PhysRevA.91.023414
Keywords: Ultrashort laser pulses